A cross-national and longitudinal analysis of handwashing and its predictors during the COVID-19 pandemic in France and Belgium. Issue 1 (31st December 2022) - Schmitz, Mathias; Wollast, Robin; Bigot, Alix; Luminet, Olivier
ABSTRACT: Background: Using a longitudinal design, we investigate how the adherence to handwashing and its underlying socio-psychological predictors evolved over time during the COVID-19 pandemic and under distinct circumstances (e.g. when the crisis was more acute or chronic). Method: We collected data ( N  = 753) in Belgium and France at the onset of the COVID-19 pandemic when the crisis was at its peak (April 2020), and almost a year later (February 2021), when the outbreak was more manageable. Results: Regression models suggest that the compliance with handwashing and its pattern of underlying predictors remained remarkably stable over time despite the variations in contextual factors such as the severity of the health crisis and the stringency of health measures. As such, the findings also highlight the robustness of the models that predict it, namely the Theory of Planned Behavior. The intentions to perform the behavior, the perceived control over it, and being part of the (para)medical field were among the strongest predictors. Conclusions: In practice, the stability of the underlying factors suggests a set of action levers that can be used in communication campaigns aimed at fostering its adherence throughout the pandemic.